2009
DOI: 10.4173/mic.2009.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Robot Control Overview: An Industrial Perspective

Abstract: One key competence for robot manufacturers is robot control, defined as all the technologies needed to control the electromechanical system of an industrial robot. By means of modeling, identification, optimization, and model-based control it is possible to reduce robot cost, increase robot performance, and solve requirements from new automation concepts and new application processes. Model-based control, including kinematics error compensation, optimal servo reference-and feed-forward generation, and servo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Lasers incur relatively lower cost and higher functional flexibility (Brogardh, 2009); lightweight, accurate, and highly reliable (Ishii, Zhao, Inami, Igarashi, & Imai, 2009); can have wider bandwidth, lower power requirements, and increased potential for covert data links in comparison with radio-based systems (Sofka, Nikulin, Skormin, Hughes, & Legare, 2009). Lasers can enable better tracking (Luber, Tipaldi, & Arras, 2011) and have inherent precision which results in better functionalities for precise collaboration.…”
Section: Overview: Advantages and Opportunities In Using Lasers For Cmentioning
confidence: 98%
See 1 more Smart Citation
“…Lasers incur relatively lower cost and higher functional flexibility (Brogardh, 2009); lightweight, accurate, and highly reliable (Ishii, Zhao, Inami, Igarashi, & Imai, 2009); can have wider bandwidth, lower power requirements, and increased potential for covert data links in comparison with radio-based systems (Sofka, Nikulin, Skormin, Hughes, & Legare, 2009). Lasers can enable better tracking (Luber, Tipaldi, & Arras, 2011) and have inherent precision which results in better functionalities for precise collaboration.…”
Section: Overview: Advantages and Opportunities In Using Lasers For Cmentioning
confidence: 98%
“…(2) Also in manufacturing, transition from welded to hydroformed beams in the frames of vehicles in the US was enabled mainly by using robots and laser cutting, significantly less costly and more flexible compared with CNC machines (Brogardh, 2009). (3) In surgery and dental operations: Lasers can minimize cellular destruction, tissue swelling, and hemostasis.…”
Section: Overview: Advantages and Opportunities In Using Lasers For Cmentioning
confidence: 99%
“…Automotive industry has stimulated the development of industrial robot control techniques. A detailed study of robot manipulators modelling and control can be found in [7] and a comprehensive overview of industrial robot control is presented in [8]. Developed control systems techniques, visual servoing [9] and new mechanical structures have been used in order to meet high productivity performance.…”
Section: Automated Robotic Work Cellmentioning
confidence: 99%
“…Recently, robot manufacturers have increased development efforts towards new applications, e.g., machining, laser welding, laser cutting and multi-robot collaboration [1], which puts forward new performance requirements on robots. The requirements, which mean high speed and high precision, can be satisfied by involving advanced model-based control schemes [2,3].…”
Section: Introductionmentioning
confidence: 99%